Barriers for Poor Cataract Surgery Uptake among Patients with Operable Cataract in a Program of Outreach Screening and Low-cost Surgery in Rural China. (June 2014) - Zhang, Xiu Juan; Jhanji, Vishal; Leung, Christopher Kai-Shun; Li, Emmy Y.; Liu, Yingpeng; Zheng, Chongren; Musch, David C.; Chang, David F.; Liang, Yuan Bo; Lam, Dennis S. C.
Abstract Aims: To identify the reasons for poor uptake of cataract surgery in a program of outreach screening and low-cost surgery in Pucheng County, a rural area in northwestern China. Methods: Detailed interviews with a semi-structured questionnaire were conducted by telephone or face-to-face for participants who had been advised to attend a low-cost cataract surgery program but did not schedule the surgery within 3 months after the initial screening. Results: Among 432 eligible subjects, 355 (82.2%) were interviewed (mean age 70.6 ± 6.6 years, 73.8% female). A total of 138 subjects (38.9%) were interviewed by phone and 217 (61.1%) were interviewed face-to-face. Lack of family support (n = 106, 29.9%) and failure to understand the need for surgery (n = 96, 27.0%) were the two main reasons for not undergoing cataract surgery. Other factors included fear of surgery (n = 62, 17.5%), lack of faith in doctors (n = 36, 10.1%), financial constraints (n = 25, 7.0%) and lack of transportation (n = 4, 1.1%). Conclusion: The principal barriers to low-cost cataract surgery uptake in rural China included lack of family support and failure to understand the need for surgery. Education targeting entire families to eliminate these barriers and development of community support systems at the family level are required to achieve greater uptake of low-cost cataract surgery programs in rural China.